SAT0258 A Prospective Evaluation of the Diagnostic Value of Conventional Radiography, Ultrasound and MRI in Comparison to Clinical Examination for the Assessment of Heel and Knee Enthesitis in Patients With Spondyloarthritis and Controls. (23rd January 2014) - Baraliakos, X.; Kiltz, U.; Heldmann, F.; Dybowski, F.; Igelmann, M.; Kalthoff, L.; Klink, C.; Krause, D.; Saracbasi, E.; Schmitz-Bortz, E.; Braun, J.
Abstract : Background: Spondyloarthritides (SpA) are characterized by inflammatory and structural changes in the axial skeleton and in peripheral joints and entheses. Imaging has an essential role in the new classification criteria for axial SpA (axSpA) but not for peripheral manifestations. This is largely due to limited knowledge about the value of imaging to detect peripheral arthritis and enthesitis in SpA and whether it differentiates SpA from other conditions (non-SpA). Objectives: To evaluate the significance of imaging procedures and their influence on treatment decision in patients with peripheral involvement of the lower limbs in SpA vs. non-SpA. Methods: The main inclusion criterion was a painful heel or knee as reported by the patients, independent of the current treatment, and age <45 years. A total of 60 patients (30 SpA: 16 with AS and 14 nr-axSpA vs. 30 non-spA) were first examined by an experienced rheumatologist, who decided on the further treatment based on the actual clinical findings. Thereafter, several imaging procedures were performed: conventional radiographs, power-doppler (PD) ultrasound (US) and magnetic resonance imaging (MRI) of the painful sites. In total 105 entheses, 71 heels and 34 knees were assessed and evaluated by the same rheumatologist. Finally the treatment decisions were re-evaluated. A systematic comparison of imaging findings was done by the Mann-Whitney-U test, and after adjustment for baseline values by multiple="multiple" regression analysis. Results: The groups were similar in mean age (37.2±6.8 years), CRP (0.6±0.9mg/dl), NRS-pain (6.1±2.1) but symptom duration (SpA: 17.2±27.5 vs. non-SpA: 4.4±4.3 months) and HLA-B27 (67% in axSpA vs. 13% in non-SpA) differed (both n<0.005). At presentation <66% of patients were taking NSAIDs, <35% DMARDs and <20% biologics in both groups. Pathologic findings were discovered most frequently using MRI of the heel (85.3% of patients), while x-rays were regarded pathologic in only 16.7% of patients (p<0.05). There were no differences in the distribution of lesions in the groups. However, bone erosions in the Achilles' insertion were seen in 48.6% of entheses in axSpA vs. 23.5% in non-SpA by US (p=0.029), and the mean patellar tendon at the tibial tuberosity was thicker in patients with SpA (38±8mm) than in non-SpA (34±5mm) as assessed by MRI (p=0.022). Based on the clinical evaluation only, a change in treatment was suggested in 47% and 57% of patients with axSpA and non-SpA, respectively. Imaging (only US and MRI) contributed to a change of medication in an additional 13% of patients with axSpA but not in non-SpA patients. Conclusions: In symptomatic patients with peripheral involvement of the knee or the heel, only erosions in the Achilles tendon area as assessed by US and thickness of the patellar tendon as assessed by MRI helped to differentiate SpA from non-SpA patients, while active enthesitis did not. Imaging of peripheral sites helped to make treatment decisions in patients with axSpA. Disclosure of Interest: None Declared